INNOVATION WITH SMALL INDUSTRY PLAYERS TO CREATE SHARED VALUE IN THE EXPERIENCE OF THE COVID-19 PERIOD IN INDONESIA - Aripin, Zaenal; Matriadi, Faisal; Ermeila, Sri (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2023)
The COVID-19 pandemic has presented serious challenges for small industry players in Indonesia, forcing them to respond with innovation to survive. In this context, collaborative innovation with small industry players is the key to creating shared value and responding to rapid economic changes. This research aims to deepen understanding of the role of innovation with small industry players during the COVID-19 period in Indonesia, exploring how this collaboration forms a business ecosystem, creates shared value, and contributes to sustainable economic growth. The research approach used is descriptive qualitative, involving in-depth interviews with small industry players, documentation analysis and case studies. Data is collected and analyzed to identify patterns, trends and impacts of collaborative innovation during COVID-19. The research results show that innovation with small industry players in Indonesia during the COVID-19 period has created a strong collaborative ecosystem. This collaboration not only responds to crises, but also forms the foundation for sustainable growth. Sharing knowledge, operational efficiency through collaboration, and the use of digital technology are the main pillars in creating shared value amidst uncertainty.